VCS parameters as diagnostic aid to Bacterial sepsis: A tertiary care experience - Abhishek Purohit; Subhadra Sharma; Ashok Mukhopadhyay; Praveen Agarwal; Ayush Gupta; Arti Kapil (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
INTRODUCTION AND METHODS : Early diagnosis of sepsis is extremely important to reduce high mortality and morbidity. In the present study,  clinical usefulness of the VCS parameters (mean channels of cell volume, conductivity, and light scatter) in neutrophils was analysed for predicting acute bacterial infection, which are obtained by the Coulter LH 750 hematology analyzer (Beckman Coulter, Fullerton, CA) during automated differential counts.